ANALISIS ASUHAN KEPERAWATAN SPIRITUALITAS PADA PASIEN KANKER PAYUDARA - Sumarni " "; Yulia Irvani Dewi; Arneliwati " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Spirituality nursing care is important because it could be influenced to guide health of daily living, improvement, as source of support for patients to face their disease. This research aims to know the description of spirituality nursing care on breast cancer patients. The design of this research was descriptive. The number of samples in this research were 20 nurses taken by using total sampling technique. The result of this research showed that there were 16 nurses didn’t make the assessment (80%), 18 nurses didn’t make nursing diagnose (90%), all of the nurses didn’t make nursing plan (100%), 16 nurses not done nursing implementation (80%),  and 19 nurses not done evaluation (95%). The result of the analysis showed that spirituality nursing care was not implemented optimally. This could be caused by there is no regulation from manager to implement spirituality nursing care. Based on this study to give suggestion to nurses manager in hospital to make policy about spiritual as a part of nursing process and to nursing institutions can be collaborate to improve nursing spiritual care. Keywords : Breast cancer, spiritual nursing care